Trading off or having it all? Completed fertility and mid-career earnings of Swedish men and women - Anne Boschini; Christina Håkanson; Åsa Rosén; Anna Sjögren (Institute for Labour Market Policy Evaluation (IFAU), 2011)
Earnings in mid-career and children are two fundamental outcomes of the life-choices of men and women. Both require time and other resources and reflect the accumulated priorities of individuals and couples. We explore how these outcomes have changed for Swedish men and women born 1945-1962 by documenting changes in education, assortative mating patterns, completed fertility and mid-career earnings. We find an overall increasing inequality in career and family outcomes of men, reflecting a rise in the family-career complementarity. For women, the family-career trade-off has eased for non-professionals, and there appears to be a convergence in the life-choices of women across education groups. Despite these different developments for men and women, we find that within-family specialization, measured by the average spousal earnings contribution, is remarkably stable through the period.
Keywords: J12; J13; J16; J24; 330; Fertility; mid-career earnings; education; gender; assortative mating; family-career trade-off; Lebensverlauf; Erwerbsverlauf; Familie-Beruf; Geschlecht; Schweden